1999
DOI: 10.1111/j.1479-828x.1999.tb03136.x
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of Perioperative Complications in 360 Patients who had Burch Colposuspension

Abstract: This retrospective study reviews intraoperative and early complications of Burch colposuspension of 360 patients. Ten patients had massive haemorrhage and 8 of them had a blood transfusion. Three patients had a haematoma. Bladder injuries were noticed in 10 patients, 3 of whom were diagnosed postoperatively. One patient had unilateral ureteral kinking. Urinary retention occurred in 20 patients for more than 10 days and 2 required catheterization for 26 and 32 days respectively. Eighteen patients had a wound in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
1
2

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 12 publications
3
11
1
2
Order By: Relevance
“…The overall incidence of complications with the Burch procedure has been reported to be as high as 40%, 10 similar to that in our study. Fortunately, wound infection, ureteral injury, hemorrhage, vesicovaginal fistula, and venous thromboembolism reported in prior series, 25,26 were not seen in our series. Patients frequently complain of postoperative pain, which may be mild and transient or severe and persistent.…”
Section: Discussioncontrasting
confidence: 47%
“…The overall incidence of complications with the Burch procedure has been reported to be as high as 40%, 10 similar to that in our study. Fortunately, wound infection, ureteral injury, hemorrhage, vesicovaginal fistula, and venous thromboembolism reported in prior series, 25,26 were not seen in our series. Patients frequently complain of postoperative pain, which may be mild and transient or severe and persistent.…”
Section: Discussioncontrasting
confidence: 47%
“…19 9 Demirci et al reported 3% transfusions and 1% haematomas. 21 In the present series, one patient required transfusion (0.3%), seven developed wound haematomas (two on anticoagulants) (1.9%) and one developed a vault haematoma (additional hysterectomy). The patient requiring transfusion had an inadvertent heparin overdose preoperation, abdominal hysterectomy and three previous continence procedures.…”
Section: Urodynamic Studies Prior To Surgerymentioning
confidence: 46%
“…We retrospectively reviewed the hospital records of 360 Burch colposuspension procedures from 1994 to 1999 in two centers, and the intraoperative and early postoperative complications were published [2]. The same women were invited to the hospitals to assess late postoperative complications and outcome.…”
Section: Methodsmentioning
confidence: 99%
“…Group I included 65 women who had undergone operations from 1998 to 1999 (mean follow-up 1.5 years), and group II included 155 women who had undergone operations from 1994 to 1997 (mean follow-up 4.5 years). The study did not include intraoperative and early postoperative complications which have been published [2].…”
Section: Methodsmentioning
confidence: 99%